Efforts to Improve Learning Outcomes of Myob Subjects Through Interactive Learning Media Based Video Tutorial for Students Class XII Accounting SMK - Aulia, Muhammad Rizki; Hidayat, Nurdin; Zainal, Vetri Yanti (Economic Education and Entrepreneurship Journal, 2024)
The problems in this research are: (1) The use of conventional learning models is not something bad, but it is felt to be less effective because students cannot realize their activeness in the learning process. (2) Students are less active in the learning process. (3) Low Myob learning outcomes. This research aims to analyze the increase in activity and learning outcomes of students using interactive learning media based on Video Tutorials in class XII Accounting in the odd semester of SMK PGRI 2 Bandar Lampung for the 2023/2024 academic year. This research is Classroom Action Research (PTK) which was held at SMK PGRI 2 Bandar Lampung in the odd semester of the 2023/2024 academic year in collaboration with the Myob class XII Accounting subject teacher. The subjects of this classroom action research are students of class Based on the research results, Myob learning using interactive learning media based on video tutorials can improve the activities and learning outcomes of class XII Accounting students at SMK PGRI 2 Bandar Lampung. This is proven by the learning activities obtained by students. The percentage increase in overall student learning activity was 74.23 (Quite Active) in cycle 1 and increased to 81.64 (Very Active) in cycle II, there was an increase in student activity from cycle I to cycle II of 7.41. Meanwhile, the student's myob learning results from cycle I to cycle II have increased and have shown the goal of the success indicator being 80%. In cycle 1 there was a percentage of learning completeness of 6 students with an average score of 72.64 (35.3%) and in cycle II there were 14 students with an average score of 79.41 (82.3%) students. which was completed by a total of 17 students, so there was an increase of 47%.Keywords: Improving Learning Activities and Outcomes, Myob Subjects, Video Tutorial-Based Interactive Learning MediaDOI: http://dx.doi.org/10.23960/E3J/v7i1.1-6